Financial Behaviour And Distress: The Impact of Religiosity, Family Influence, and Locus of Control - Kasanah, Roisatun (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
This study aims to determine the factors that influence financial behavior and financial distress in Muslim families in the city of Surabaya. The variables selected in this study are religiosity, family financial socialization, and locus of control. The research method used in the study is a survey method using a questionnaire as an instrument to obtain data. Data analysis was carried out using the SMART PLS application with a sample size of 100. The results of the study showed a positive and significant relationship between family financial socialization and locus of control on financial behavior while religiosity was found to have a positive but insignificant relationship on financial behavior. This study also found that the variables of religiosity, family financial socialization, locus of control, and financial behavior did not have a significant relationship on financial distress.